Evaluasi implementasi standar operasional prosedur dokumen transaksi terhadap keakuratan pencatatan akuntansi: Studi Kasus pada PT BUU - Talitha Raissa Asmawati; Tituk Diah Widajantie (Nur Science Institute, 2025)
This study aims to evaluate the implementation of Standard Operating Procedures (SOPs) for purchase invoices, sales invoices, and delivery orders to ensure the accuracy of accounting records at PT BUU. A qualitative approach with a case study method was employed through in-depth interviews, direct observation, and document analysis. The results reveal that the implementation of SOPs has not been consistently applied across departments, particularly in the submission and validation of physical documents. Delays and document loss have affected the timeliness and reliability of accounting records. These findings reinforce the COSO Internal Control Framework, emphasizing the importance of control and monitoring activities, and the Policy Theory, which highlights that SOP effectiveness depends on employee compliance and managerial support. The study recommends strengthening internal supervision through a digital document tracking system and regular training to enhance procedural adherence and the accuracy of financial reporting.